Possible involvement of Toll-like receptor 8-positive monocytes/macrophages in the pathogenesis of Sjögren’s disease - Yan, Lijing; Miyahara, Yuka; Sakamoto, Mizuki; Kaneko, Naoki; Chen, Hu; Sameshima, Junsei; Kido, Hajime; Yokomizo, Shiho; Sueyoshi, Tomoki; Nagano, Haruki; Ohyama, Yukiko; Nakamura, Seiji; et al. (Frontiers in Immunology, 2024)
Background: Sjögren's disease (SjD) is an autoimmune disease marked by lymphocytic infiltration of salivary and lacrimal glands, leading to glandular dysfunction, where CD4-positive helper T (Th) cells and their cytokines are crucial in the pathogenesis. Recent studies have demonstrated that Tolllike receptors (TLRs), particularly those recognizing immune complexes containing DNA and RNA, contribute to Th cell activation in various autoimmune diseases. This study explores the expression and function of these TLRs in SjD.Methods: DNA microarray analysis of salivary gland tissue from six SjD patients and real-time PCR (n = 32) was used to identify overexpressed TLRs. Single-cell RNA sequencing (scRNA-seq) was performed using tissue lesions and integrated with published scRNA-seq data from tissues and peripheral blood mononuclear cells to examine gene expression in macrophages and monocytes.Finally, multi-color immunofluorescence staining was conducted to confirm TLR8 expression and function in SjD lesions (n = 19).Results: DNA microarray analysis revealed the up-regulation of TLR8, along with other TLRs and innate immune response genes in SjD. Real-time PCR showed significant up-regulation of TLR7 and TLR8. TLR8 up-regulated in both analyses. In scRNA-seq analysis, the TLR8-expressing cluster comprised macrophages and monocytes, which also produced T cell activation genes like CD86.TLR8-positive macrophages infiltrated inflammatory sites and frequently expressed CD86 in quantitative imaging approaches.Conclusions: These results suggest that infiltrating monocytes and macrophages may produce cytokines and chemokines through TLR8 stimulation, potentially enhancing B7 molecule expression, promoting the adaptive immune response, and contributing to SjD pathogenesis.